The role of punctuation in P2P lending: Evidence from the People's Republic of China - Xiao Chen; Bihong Huang; Dezhu Ye (Asian Development Bank Institute (ADBI), 2017)
This paper investigates the role of punctuation in the peer-to-peer (P2P) lending market. Using data from Renrendai, one of the largest P2P lending platforms in the People's Republic of China, we investigate how the amount of punctuation used in loan descriptions influences the funding probability, borrowing rate, and default. The empirical evidence shows that the amount of punctuations is negatively associated with the funding probability and borrowing rate. We propose that the usage of punctuation affects the readability of a loan description and reflects borrowers' self-control and cognitive ability. Within a given number of words, excessive usage of punctuation makes loan description informal and reduces the readability of the text, thereby impairing investors' trust in borrowers. Moreover, borrowers that overuse punctuation may have lower ability of self-control, and tend to underestimate the risk of borrowing and offer lower borrowing rate due to overconfidence.
Keywords: G10; G11; G14; G20; G23; G29; 330; P2P lending; information asymmetry; word; punctuation